PENGARUH PENDEKATAN PEMBELAJARAN DAN GAYA KOGNITIF TERHADAP HASIL BELAJAR MATEMATIKA - -, SURYADI (Program Studi Magister Pendidikan Anak Usia Dini, 2017)
: The purpose of this study is to determine the effect of learning approach and cognitive style on learning outcomes in mathematics studies class 3 elementary students, This study is uses design by factorial 2 x 2. The samples are consisted of 69 student. The technique of data analysis are two ways analysis of variance (ANAVA) and followed by Tuckey's test for significance level of Î± = 0, 05. To test the normality of the data using Lilliefors test and to test the homogeneity of the data using the Bartlett test. Research results obtained are: 1) the results of mathematics studies in the group of students who were given a type of learning approach realistic mathematics education is higher than the group of students who were given problem based learning approach, 2) the resualts of mathematics studies in the group of students who have cognitive style field Independent is higher than the group of students who have cognitive style filed dependent, 3) there is an interaction effect between the approach learning and cognitive style the results of mathematics studies, 4) Group of students who have cognitive style filed independent their mathematic studies result will be higher if it is teached by using a mathematic realistic approach than problem based learning approach, 5) Group of students who have cognitive style filed dependent their mathematic studies result will be higher if it is teached by using a problem based learning approach than mathematic realistic approach, 6) in process learning using mathematic realistic approach their mathematic studies result will be higher in who have cognitive style filed independent student than who have cognitive style filed dependent, 7) in process learning using problem based learning approach their mathematic studies result will be higher in who have cognitive style filed dependent student than who have cognitive style filed independent. Keywords: learning approach, cognitive style, mathematic studies result